Laboratory study on the leaching potential of spent alkaline batteries using a MSW landfill leachate - Susana Xará (2013)
Two leaching tests were carried out, one with whole batteries and another with cross-cut batteries. In both cases, NEN 7343 (a Nederland's Standard) procedure was followed using a municipal solid waste (MSW) landfill leachate as extraction solution. Seven fractions were collected corresponding to cumulative liquid/solid (L/S) ratio from 0.1 to 10.0. Those fractions were separately characterized in terms of pH, conductivity, redox potential, density, sulphate, chloride, As, Cd, Co, Cr, Cu, Fe, Hg, Mn, Ni, Pb, Sb, Tl and Zn. Results showed that the influence of the alkaline batteries in the landfill leachate composition varies with their physical integrity and with the L/S ratio, and several variations were observed throughout the tests. The leachate pH and redox potential increased as result of the contact with batteries, particularly pH in the test with the cross-cut batteries. The leachate density and conductivity did not change significantly with the whole batteries, in contrast with the test with cross-cut batteries.